Diversity of cyclic ureide compound-, dihydropyrimidine-, and hydantoin-hydrolyzing enzymes in Blastobacter sp. A17P-4 - Ogawa, Jun; Honda, Michinari; Shimizu, Sakayu; Soong, Chee Leong (Oxford University Press, 1995)
Two cyclic ureide compound-hydrolyzing enzymes were found in Blastobacter sp. A17p-4, and partially purified. One hydrolyzed 5-substituted hydantoins D-stereospecifically and had dihydropyrimidinase activity. The other was a novel enzyme which should be called an imidase. The imidase preferably hydrolyzed cyclic imide compounds such as glutarimide and succinimide more than cyclic ureide compounds, and produced monoamidated dicarboxylates. © 1995, Japan Society for Bioscience, Biotechnology, and Agrochemistry. All rights reserved.